Protective Effect of Znt7 on High Glucose-Induced Epithelial-to-Mesenchymal Transition in Renal Tubular Epithelial Cells - Xiuli Zhang; Xu Lian; Dan Liang; Lianzhi Zhang; Shengquan Liu; Lina Yang; Zhi-Hong Chi; Harvest F. Gu (Karger Publishers, 2018)
Background/Aims: Evidence from our and other groups has demonstrated that zinc transporter 7 in SLC30 family (ZnT7) inhibited epithelial-to-mesenchymal transition (EMT) and apoptosis in rat peritoneal mesothelial cells (RPMCs) under high glucose (HG) concentration. In the present study, we investigated the effect of ZnT7 on EMT of renal tubular epithelial cells (RTECs) in an in vitro model of diabetic nephropathy (DN). Methods: A dual-fluorescent staining protocol was used for detection of ZnT7 in a normal rat kidney tubular epithelial cell line (NRK-52E cells). EMT was induced with HG (30 mM). NRK-52E cells were transfected with plasmids codifying for hZnT7-EGFP and interfering RNA for determination of the effect of ZnT7 over-expression and silencing, respectively. Expression of ZnT7, activation of the MAPK/ERK and TGF-β/Smad pathways were analyzed with by means of Western blot. Results: ZnT7 was localized in the perinuclear region and Golgi apparatus. In HG-induced EMT of NRK-52E cells, ZnT7 was up-regulated. Over-expression of ZnT7 led to inhibition of HG-induced EMT, while knock-down of ZnT7 increased EMT. Furthermore, knock-down of ZnT7 and increased HG-induced EMT was accompanied by activation of the MAPK/ERK and TGF-β/Smad pathways. Conclusion: The present study provides evidence that ZnT7 has a protective effect over EMT of RTECs in DN and suggests that the inhibition of HG-induced EMT may be achieved through the MAPK/ERK and TGF-β/Smad pathways. Thereby, ZnT7 could be a potential target for translation medicine and prevention program in DN.